Assessment of Mental Health and Mental Health Literacy Among Medical Students of HITEC-IMS - Farooq, Sidra; Bibi, Anwar; Basim, Furqan; Khan, Waqas; Sani, Abdul Rehman; Ali, Muhammad Shoaib; Ahmed, Aashi (Pakistan Armed Forces Medical Journal, 2024)
Objectives: To Assess Mental Health and Mental Health Literacy among medical students in HITEC-IMS, evaluate their relation to sociodemographic variables, and determine the correlation between Mental Health and Mental Health Literacy. Study Design: Cross-sectional study. Place and Duration of Study: Department of Community Medicine, HITEC-IMS, Taxila Pakistan, from Nov 2023 to Apr 2024. Methodology: Two hundred six participants from MBBS students of HITEC-IMS participated, using a consecutive sampling method (five groups based on year of study). The structured proforma with three parts was used, the first part started with collecting demographic variables. The second part consisted of the pre-validated Mental Health Literacy Scale for assessing Mental Health Literacy, and the third part included the Warwick-Edinburgh Mental Well-Being Scale for evaluating mental health. SPSS version 28 was used for data analysis. Results: Out of total students, 92(41.8%) students were males and 128(58.2%) were females. However, 85(38.6%) students had mild Mental health, 131(59.5%) had moderate mental health and 4(1.8%) had high mental health. Furthermore, 134(60.9%) students had low mental health literacy, 38(17.3%) had below average, 45(20.5%) had average and 3(1.4%) had above average. Correlation between Mental Health and Mental Health Literacy resulting in a considerable positive correlation (r=0.192, p=0.004). Conclusions: Mental Health Literacy is an important concept, with its relation to Mental Health, highlighting the need for timely interventions necessary for the improvement of Mental Health Literacy, and to achieve meaningful outcomes in the realm of Mental Health.